PENERAPAN APLIKASI GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN ONLINE MATEMATIKA SELAMA PANDEMI COVID-19 DI SMA NEGERI 1 TONGAS - Pratiwi Dwi Warih Sitaresmi; Ratna Damayanti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The outbreak of the Corona virus or Covid-19 in Indonesia since March 2020 has affected various aspects of life, especially education in Indonesia. One of the government's policies to suppress the spread of the Corona virus is to close school activities. Online learning is a solution to overcome the challenges of face-to-face learning. The Google Classroom application is an application created by Google specifically developed to support the implementation of online learning. The subjects of this study were 87 students of class 11th. The instrument used was a mathematics achievement test and a questionnaire. The data analysis technique uses descriptive qualitative data analysis, where student learning outcomes achieve learning completeness of at least 70%. The results showed that 59.77% of students were very happy with the implementation of Google Classroom when learning Mathematics during the pandemic, and 56.32% of students felt happy when doing independent assignments given through Google Classroom. 56.32% of students feel interested in the mathematics learning process. 62.07% of students find it easy to apply the Google Classroom application in the Mathematics learning process. However, based on the results of several indicators, some students think that face-to-face learning is still very much needed. In addition, teachers are required to support the activities of their students to stay motivated to engage in online learning.